(untitled) (Economic and Political Thought, 2020)
The aim of this paper is to analyse the relationship between the determinants of technological innovation and economic growth. Moreover, it is aimed at examining whether expenditures on R&D variable has a stronger impact on economic growth, comparing to other determinants of technological development. The primary reason to choose the topic is that we are living in a century of notable technological change and investigating the relationship between technology progress and economic development is the way to find new methods of accelerating economic growth. The literature on this topic is extremely rich and many authors claim that the main driver of long-term economic growth is technological innovation. Furthermore, over the previous fifty years, a key financial finding has been that technological progress is crucial to long-term economic growth. This paper uses panel data for 19 developed countries over the period of 45 years (1973–2017) to examine the effect of such variables as expenditures on R&D, panel applications and R&D personnel on GDP per capita. The paper uses panel Bayesian Model Averaging under weak exogeneity. The results obtained show that all three indicators of technological innovation have a positive impact on per capita GDP and that expenditures on R&D have the strongest effect on economic growth.